2020
DOI: 10.1038/s41467-020-19026-y
|View full text |Cite
|
Sign up to set email alerts
|

A causal role for frontal cortico-cortical coordination in social action monitoring

Abstract: Decision-making via monitoring others’ actions is a cornerstone of interpersonal exchanges. Although the ventral premotor cortex (PMv) and the medial prefrontal cortex (MPFC) are cortical nodes in social brain networks, the two areas are rarely concurrently active in neuroimaging, inviting the hypothesis that they are functionally independent. Here we show in macaques that the ability of the MPFC to monitor others’ actions depends on input from the PMv. We found that delta-band coherence between the two areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 67 publications
(116 reference statements)
6
54
0
Order By: Relevance
“…This model has recently received direct support from simultaneous recordings and chemogenetic manipulations of neuronal activity in the F5-to-F6 neural circuit, demonstrating that coordinated activity along this pathway has a causal role in social action monitoring. 59 How do the key functional properties of the distinct nodes of the AON considered thus far map onto different cell classes? A null hypothesis would assume that distinct visuomotor functional properties are equally represented by different sets of neurons distinguished by their extracellular spike shape.…”
Section: Discussionmentioning
confidence: 99%
“…This model has recently received direct support from simultaneous recordings and chemogenetic manipulations of neuronal activity in the F5-to-F6 neural circuit, demonstrating that coordinated activity along this pathway has a causal role in social action monitoring. 59 How do the key functional properties of the distinct nodes of the AON considered thus far map onto different cell classes? A null hypothesis would assume that distinct visuomotor functional properties are equally represented by different sets of neurons distinguished by their extracellular spike shape.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in specific neuronal manipulation tools have drastically enhanced our understandings of the functional roles of individual neural pathways in small animals such as rodents (24,53). Nonetheless, the application of pathway-selective manipulations to non-human primates is still largely limited by using either optogenetic terminal activation (19)(20)(21) or double-vector methods (15)(16)(17)(18), neither of which is capable of testing dissociable function of multiple neural pathways in individual subjects. Using a chemogenetic approach, the current study succeeded in the double-dissociation of the roles of two distinct pathways in individual monkeys.…”
Section: R a F Tmentioning
confidence: 99%
“…Several studies have so far shown behavioral modification with reversible pathway-selective dissection in monkeys, where a double-viral vector infection method was used to manipulate the activity of a single neuronal pathway (15)(16)(17)(18). This approach, however, is not suitable for investigating multiple neural pathways independently within a single animal.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have generated interest in the role of midfrontal oscillations in goal-directed interpersonal motor interactions (Ninomiya et al, 2018; 2020) and a specific role of humans’ frontal theta during interpersonal reaching interactions (Moreau et al, 2020). In the present study we investigated this issue from a causative approach, capitalizing on the combination of tACS and virtual reality.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indeed indicates that the MFC is involved in interpersonal performance monitoring (Bekkering et al, 2009; see Ninomiya et al, 2018 for review). Additionally, recent studies in monkeys highlighted a role of cortico-cortical premotor and medial prefrontal network for the execution of interactive tasks (Sliwa et al, 2017; Ninomiya et al, 2020). However, whether the ability to monitor and react to the behaviour of a partner causally depends on midfrontal theta remains unknown.…”
Section: Introductionmentioning
confidence: 99%